2006
DOI: 10.1371/journal.pgen.0020094
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear mRNA Degradation Pathway(s) Are Implicated in Xist Regulation and X Chromosome Inactivation

Abstract: A critical step in X-chromosome inactivation (XCI), which results in the dosage compensation of X-linked gene expression in mammals, is the coating of the presumptive inactive X chromosome by the large noncoding Xist RNA, which then leads to the recruitment of other factors essential for the heterochromatinisation of the inactive X and its transcriptional silencing. In an approach aimed at identifying genes implicated in the X-inactivation process by comparative transcriptional profiling of female and male mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 36 publications
1
41
0
Order By: Relevance
“…The decrease in the level of Kcnq1ot1 RNA along the length of the transcription unit might be the result of several unmapped polyadenylation sites within the transcript; alternatively, transcription might be impeded by a non-permissive chromatin structure. By comparison, the Air RNA is 108 kb long and largely unspliced (Lyle et al, 2000;Seidl et al, 2006), whereas the Xist RNA is spliced from 23 kb to 17.9 kb, and this splicing may be needed for Xist-mediated epigenetic silencing (Ciaudo et al, 2006). Quantification of nuclear and cytoplasmic RNA from primary MEFs showed that Kcnq1ot1 RNA is significantly enriched in the nucleus relative to the cytoplasm (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…The decrease in the level of Kcnq1ot1 RNA along the length of the transcription unit might be the result of several unmapped polyadenylation sites within the transcript; alternatively, transcription might be impeded by a non-permissive chromatin structure. By comparison, the Air RNA is 108 kb long and largely unspliced (Lyle et al, 2000;Seidl et al, 2006), whereas the Xist RNA is spliced from 23 kb to 17.9 kb, and this splicing may be needed for Xist-mediated epigenetic silencing (Ciaudo et al, 2006). Quantification of nuclear and cytoplasmic RNA from primary MEFs showed that Kcnq1ot1 RNA is significantly enriched in the nucleus relative to the cytoplasm (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…For example, UPF1 was shown to affect the stability of both PTC-and non-PTC-containing mRNAs in earlier work (Bhattacharya et al 2000;He and Jacobson 2001). Recent studies identified a role for UPF1 in the stability of the intronless histone H2a mRNA in a cell-cycle-dependent manner in mammalian cells (Kaygun and Marzluff 2005) and an effect on Xist RNA, but in this latter case, this RNA is entirely restricted to the nucleus (Ciaudo et al 2006). While there is at least one similarity between NMD and the effects of UPF1 on H2A and HIV-1 RNA, including the dependence on UPF1 expression and ongoing translation (Fig.…”
Section: Upf1 Colocalized With Pr55mentioning
confidence: 98%
“…The ability of UPF1 to shuttle between the nucleus and cytoplasm (Mendell et al 2002) and its role in nonsense-mediated alternative exon skipping (Mendell et al 2002), in exon skipping (Wang et al 2002), in regulating nuclear Xist RNA (Ciaudo et al 2006), and in DNA repair (Azzalin and Lingner 2006), all support nuclear roles. Our results suggest that UPF1 is needed for late gene expression stages of HIV-1, early following transcription to protect the viral mRNA from degradation.…”
Section: Upf1 Colocalized With Pr55mentioning
confidence: 99%
“…Finally, female mouse embryonic stem cell lines depleted for RENT1 (the murine ortholog of UPF1) or for UPF2 fail to form Xist RNA domains upon differentiation and to undergo X-inactivation, suggesting possible broad roles for nuclear SMG proteins in chromatin organization pathways that involve RNA. 44 Chromatin state. As already mentioned, mammalian telomeres are enriched in heterochromatic marks including H3K9me3, H4K20me3 and HP1.…”
Section: Terra Regulatory Pathwaysmentioning
confidence: 99%